Critically ill Covid-19 patients with acute kidney injury: A single-center cohort study - Şahintürk, Helin; Kandemir, Emre; Ensarioglu, Mesher; Yeşiler, Fatma İrem and Gedik, Ender and Zeyneloglu, Pınar (Journal of Surgery and Medicine, 2021)
Background/Aim: Acute kidney injury (AKI) is a common serious complication associated with morbidity and mortality in critically ill COVID-19 patients. Although there is very limited data on the incidence of AKI in this cohort, conflicting results were recently reported. The incidence of AKI in critically ill COVID-19 patients ranged between 0.5-50% in the early studies. This study aimed to evaluate the incidence and determine the demographic parameters, clinical courses, and outcomes of AKI in critically ill COVID-19 patients admitted to the intensive care unit (ICU). Methods: After ethics committee approval was obtained, critically ill COVID-19 patients admitted to our ICU between June 1- December 30, 2020, were analyzed in this retrospective cohort study. Patients over the age of 18 years who were admitted to the intensive care unit with the diagnosis of COVID-19 or whose real-time polymerase chain reactions (RT-PCR) test were positive were included in the study. Incidence and stages of AKI among the included critically ill COVID-19 patients were evaluated. The patients were divided into two groups according to the presence of AKI to define the risk factors and clinical outcomes. AKI was defined according to the Kidney Disease Improving Global Outcomes (KDIGO) guidelines based on serum creatinine and urine output. Results: We analyzed seventy-four critically ill confirmed COVID-19 patients. The mean age was 70.7 (14.8) years and 63.5% were male. Thirty-four patients (45.9%) had AKI, 12 patients in stage I (16.2%), 13 patients in stage II (17.6%), and 9 patients in stage III (12.1%). Renal replacement therapy (RRT) was initiated in 28.4% of patients with AKI; 16.2% received intermittent hemodialysis and 12.2%, continuous renal replacement therapy. APACHE II score and GCS at ICU admission were similar in patients with or without AKI (P>0.05), but the SOFA score was significantly higher in patients with AKI (P=0.03). ARDS and shock were significantly higher in patients with AKI than without (P=0.01 and P=0.039, respectively). Compared to the patients without AKI, those with AKI required higher amounts of oxygen therapy (high-flow oxygen therapy, non-invasive mechanical ventilation) and invasive mechanical ventilation (P=0.01 and P<0.001). The ICU mortality was 61.8% for the AKI group compared to 20% among those without (P<0.001). Conclusions: Our study showed that AKI and renal replacement therapy are common in critically ill COVID-19 patients. SOFA score, ARDS, and shock rates were significantly higher among patients who developed AKI. The presence of AKI was associated with higher amounts of oxygen therapy and increased invasive mechanical ventilation. The severity of illness at ICU admission and ICU mortality were higher among those with AKI. Since AKI is seen in almost one in two patients and its development is associated with higher mortality, urine output, and creatinine values should be closely monitored in critically ill COVID-19 patients. It is recommended not to delay RRT therapy as soon as stage 2 AKI develops to preserve kidney function. In addition, optimal hemodynamic monitoring with appropriate fluid management and vasopressor drugs is required to ensure adequate renal perfusion.